A liberdade de expressão e o pluralismo no constitucionalismo contemporâneo - Araújo, Marilene (2016)
Summary: No pluralism there is no effective exercise of the right to freedom of expression, being the regular law such freedom via constitutional system. The law, communication and human sociality are inextricably linked. Humanity without communicational interactions can not exist. The very human dignity is only possible with the preservation of freedom and communication, and freedom of expression appears as power to act human. In social terms the various networks of conversations where emerging culture means that there is a plurality of opinion, cultures. The more free speech, more plurality and the more plurality, more freedom of expression. It is a circular and complex way. Freedom of expression currently understood is a construct and not a given post. Greece was the right to speak in the Agora. A revolution of the media does this freedom go through the emergence of the press and the revolutions of the eighteenth century. The result is positivization this freedom through international and constitutional documents. A second revolution is the technology of electromagnetic waves and the emergence of radio and television, once again the law regulates via grants system and the public service institute. Constitutions and American, French and German jurisprudence buildings bring notions of freedom of expression from the perspective of pluralism. Similarly, the European and American human rights protection system does. The Brazil supported in its constitution and in international treaties have a protection system which includes the freedom of expression and pluralism, but still faces problems for the realization of this right. The challenges are many, because now comes a third revolution of the medium with the arrival of the internet, the market players. But any proposal must pass the non divisibility of social and individual sphere. The law can regulate and carry out increasingly setting such freedom, punishing, rewarding and offering subsidies for realization of freedom of expression